Admission of guilt under Section 24 of the Evidence Act 1950 (Act 56) / Noorzilan Mohamed Noor - Mohamed Noor, Noorzilan (Faculty of Law, 1986)
The aim and purpose of this paper is to examine what is a confession and when can it be considered as voluntary therefore admissible in evidence and particularly to test the nature of voluntariness when made to a person in authority. What the word 'confession' implies has nowhere been defined in law but the mention of this word occurs in the Evidence Act is Sections 24 to 30, which sections are set down hereunder: "Section 24. A confession made by an accused person is irrelevant in a criminal proceeding,if the making appears to the Court to have been caused by any inducement, threat or promise having reference to the charge against the accused person,proceeding from a person in authority and sufficient in the opinion of the Court, to give the accused person grounds which would appear to him reasonable for supposing that by making it he would gain any advantage or avoid any evil of a temporal nature in reference to the proceeding against him. Section 25(1) subject to any express provision conr tained in any written law, no confession made to a police officer shall be proved as against a person accused of any offence